CDS and bank ownership structures: does the credit side show who advocates more risk?. Issue 2 (21st March 2016) - Froneberg, Dennis; Kiesel, Florian; Schiereck, Dirk
Abstract : Purpose: This study aims to investigate whether ownership compositions effect credit risk profiles of banks prior to and during the financial crisis. In detail, this study examines whether more powerful owners of a bank impact the credit risk profile. Design/methodology/approach: The effects of the ownership structure on credit risk are estimated using credit default swap (CDS) spreads. Therefore, 86 global privately held and publicly listed banks from 23 countries are considered in a panel analysis for the period 2005-2008. Findings: The results indicate that banks with a more concentrated ownership structure tend to be riskier, as they have larger CDS spreads. Furthermore, we observe that bank regulation has a negative impact on banks' credit risk. Larger banks exhibit significantly lower risk than smaller banks. Originality/value: These findings are of high relevance for the respective national regulative environment and for the respective financial institutions themselves. Regulatory bodies have to be aware of whether certain ownership compositions lead to a significant risk factor and which risk indicators exhibit the risk more precisely and in timely fashion.